The Enhancement of Fingerprint Images using Gabor Filter. (March 2019) - Erwin,; Karo, Nina Nuria Br.; Yulia Sari, Asti; Aziza, Nur; Kesuma Putra, Hadrians
Abstract: Fingerprint is used as an object of the image that can be characteristic of every human being. Fingerprint images that have noise, blur and are not clearly a major problem in image processing. Enhancement of fingerprint image quality is proposed with the Gabor Filter method. The steps taken begin by increasing the local image contrast by applying the adaptive histogram equalization (AHE) method, then, corrected by the Gabor Filter and binarization methods. Image quality improvement was measured by peak signal to noise ratio (PNSR) and mean square error (MSE). The results of the experiment using the NIST dataset resulted in the best value of PNSR of 18.2692 and MSE of 159.3449.